2000
DOI: 10.1177/10547730022158582
|View full text |Cite
|
Sign up to set email alerts
|

Patient Life Stories and Current Situation as Told by Carers in Nursing Home Wards

Abstract: Knowing a patient's life story is important for good nursing care of frail and vulnerable elderly people with cognitive impairments. The aim of the study was to compare patients' life stories and current situations as told by carers before and after 1 year of supervision, in which the Resident Assessment Instrument was used as a basis for individualized nursing care. Qualitative content analysis was used to disclose changes and to enable descriptions of patterns. After the intervention, two overall perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 30 publications
1
70
0
1
Order By: Relevance
“…Mairis (1994) holds that dignity is developed through life experiences, and in line with this ± and as emphasized by carers ± knowledge of patients' background, lived experiences as well as current situations and conditions is important (cf. Hansebo & Kihlgren, 2000a). Carers enabled patients to feel a sense of dignity when they were allowed to be good at something, however small their capabilities might be, as well as when their selfrespect was protected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mairis (1994) holds that dignity is developed through life experiences, and in line with this ± and as emphasized by carers ± knowledge of patients' background, lived experiences as well as current situations and conditions is important (cf. Hansebo & Kihlgren, 2000a). Carers enabled patients to feel a sense of dignity when they were allowed to be good at something, however small their capabilities might be, as well as when their selfrespect was protected.…”
Section: Discussionmentioning
confidence: 99%
“…These opinions have been con®rmed in a review of nursing records (Hansebo et al, 1999). Furthermore, a study of patients' life stories as told by carers indicated a clearer perception of the patient as a unique person after the intervention, together with a more explicit awareness among the carers of their own professional approach (Hansebo & Kihlgren, 2000a). In video-recorded morning care sessions of four carers, skills in supporting and con®rming nursing care improved across the intervention (Hansebo & Kihlgren, 2000b).…”
Section: Introductionmentioning
confidence: 96%
“…Polit & Hungler 1999). Every 10th of the 30 stories before and after the intervention was chosen for co‐assessment by a researcher (Hansebo & Kihlgren 2000).…”
Section: Patient Life Stories and Current Situationmentioning
confidence: 99%
“…The photographs and memorabilia can be used therapeutically to enhance communication between health professionals, residents, caregivers and their families. These LSB can highlight a resident’s unique life history (Hewitt 2000), and be used as a basis for individualized care (Hansebo and Kihlgren 2000). Anderson and colleagues (1992) suggested that it can help to improve assessment and assist in the building of relationships as people listen to each other’s stories (Hansebo and Kihlgren 2000).…”
Section: Life Story Booksmentioning
confidence: 99%
“…These LSB can highlight a resident’s unique life history (Hewitt 2000), and be used as a basis for individualized care (Hansebo and Kihlgren 2000). Anderson and colleagues (1992) suggested that it can help to improve assessment and assist in the building of relationships as people listen to each other’s stories (Hansebo and Kihlgren 2000). LSW has the potential to provide a greater insight into a person’s needs and behaviors (Johnson 1976; Clarke et al 2003), providing people with a voice and it may help challenge attitudes and beliefs about people (Meninger 2006).…”
Section: Life Story Booksmentioning
confidence: 99%